1979
DOI: 10.1111/j.1558-5646.1979.tb04742.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Ecological Character Displacement in Western American Catostomid Fishes

Abstract: Much of recent ecological theory rests petition with individuals of another popon the assumption that the primary factor ulation in the same environment. The responsible for the organization of natural characters may be morphological, ecologcommunities, particularly of animals, is ical, behavioral, or physiological and the interspecific competition (e.g., Mac-change may be either divergent or con- Arthur, 1972; Schoener, 1975). The valid-vergent. By divergent competitive charity of this assumption depends almo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…While geographic size clines are common (Rosenzweig 1968;Ralls & Harvey 1985;Meiri & Dayan 2003;Meiri, Dayan & Simberloff 2005a;Meiri, Yom-Tov & Geffen 2007b;Haba et al 2008;Gu¨r 2010), few studies have tried to correct for their presence while studying character displacement. Dunham, Smith & Taylor (1979) examined character displacement in Catostomus fishes, controlling for geographic clines tracking several variables (e.g. latitude, elevation).…”
Section: Introductionmentioning
confidence: 99%
“…While geographic size clines are common (Rosenzweig 1968;Ralls & Harvey 1985;Meiri & Dayan 2003;Meiri, Dayan & Simberloff 2005a;Meiri, Yom-Tov & Geffen 2007b;Haba et al 2008;Gu¨r 2010), few studies have tried to correct for their presence while studying character displacement. Dunham, Smith & Taylor (1979) examined character displacement in Catostomus fishes, controlling for geographic clines tracking several variables (e.g. latitude, elevation).…”
Section: Introductionmentioning
confidence: 99%
“…The role of resource competition in promoting phenotypic divergence between interacting species is difficult to demonstrate empirically, however (Conner and Simberloff 1979;Dunham et al 1979;Schluter and McPhail 1992;Grant 1994;Schluter 1994Schluter , 2000Losos 2000). Experimental tests are generally not feasible because it often takes a long time to observe an evolutionary response to selection imposed by competitors.…”
mentioning
confidence: 99%
“…If the characters associated with resource partitioning have a genetic basis, character displacement is said to have occurred (Brown and Wilson 1956). Although divergence between sympatric species is the most commonly identified form of character displacement, convergence of traits, presumably to enhance competitive ability in a particular environment, is also included in the theory of character displacement (Grant 1972;Dunham et al 1979).…”
mentioning
confidence: 99%
“…It is commonly accepted that community structure can affect the niche and morphological characteristics of an or-ganism. Correspondingly, several studies of character displacement in vertebrates have investigated the phenomenon of character change in relation to community composition (review in Grant 1972;Dunham et al 1979;Strong et al 1979;Hendrickson 1981;Dayan et al 1990;Werdelin 1996). Although some of the initial and best-known studies of community-wide character displacement have considered island biota (Lack 1947;Schoener 1969;Williams 1972), recent studies have shown that this phenomenon is also likely to occur in continental communities (Dayan et al 1990;Werdelin 1996;Ben-Moshe et al 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation